O discurso paródico no Cristo de José Saramago - Ferreto, Alcina Aparecida Molina (2007)
The purpose of this dissertation is to analyze the parody on the novel O Evangelho Segundo Jesus Cristo by José Saramago. We pretend to establish a comparison between Jesus from the gospel s tests and Jesus made by Saramago, emphasizing the through test speech, which is used as a basis for dialog mechanisms, responsible for the critic-metalanguage-ironic of saramagy writing. The objective of this work is to make a reading of Jesus made by Saramago, trying to define the main difference between him and his gospel homonym. From all this mentioned above, we will demonstrate that the saramagy hero is a recreation of his model basis more human, which is the result from reading with criticism and irony of the biblike narrative again: the new character denies the values that characterize the Bible used to make this parody. This profaned version of Christ configurates as a twisted and uncharacterized image of this gospel character, imposing like a new model as much as from the human being as from the divine